2010
DOI: 10.1002/bdrb.20250
|View full text |Cite
|
Sign up to set email alerts
|

Development in the cynomolgus macaque following administration of ustekinumab, a human anti‐il‐12/23p40 monoclonal antibody, during pregnancy and lactation

Abstract: Exposure of macaque fetuses and infants to ustekinumab had no adverse effects on pre- and postnatal development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(63 citation statements)
references
References 40 publications
5
55
0
2
Order By: Relevance
“…Ustekinumab is a US FDA class B medication, primarily based on animal studies in cynomolgus monkeys and with limited human data 6,59,60. Evaluation of the 29 pregnancies reported with maternal use of ustekinumab (at least 1 dose) from 4 psoriasis studies demonstrated no congenital anomalies, a rate of spontaneous abortion comparable to the general population (15%–20%), and no association between a longer duration of ustekinumab exposure before the reported pregnancy and adverse outcomes 61.…”
Section: Drug Developmentmentioning
confidence: 99%
“…Ustekinumab is a US FDA class B medication, primarily based on animal studies in cynomolgus monkeys and with limited human data 6,59,60. Evaluation of the 29 pregnancies reported with maternal use of ustekinumab (at least 1 dose) from 4 psoriasis studies demonstrated no congenital anomalies, a rate of spontaneous abortion comparable to the general population (15%–20%), and no association between a longer duration of ustekinumab exposure before the reported pregnancy and adverse outcomes 61.…”
Section: Drug Developmentmentioning
confidence: 99%
“…The administration of high doses of ustekinumab to cynomolgus monkeys during pregnancy and lactation had no adverse effects on females or fetuses. In this animal model, abortion rates were the same with and without exposure to the drug [12]. According to medication characteristics, it is preferable to avoid ustekinumab during pregnancy, and women of childbearing age should use effective contraception during and up to 15 weeks after treatment [13].…”
Section: Discussionmentioning
confidence: 99%
“…Two fetal development studies of ustekinumab conducted in cynomolgus macaques have revealed no evidence of maternal toxicity, embryotoxicity, or teratogenicity [107]. There are very limited data on the safety of ustekinumab treatment during pregnancy.…”
Section: Ustekinumabmentioning
confidence: 99%